2015
DOI: 10.1155/2015/316235
|View full text |Cite
|
Sign up to set email alerts
|

Curbing Inflammation in Skin Wound Healing: A Review

Abstract: Wound healing is a complex regulated process that results in skin scar formation in postnatal mammals. Chronic wounds are major medical problems that can confer devastating consequences. Currently, there are no treatments to prevent scarring. In the early fetus wounds heal without scarring and the healing process is characterized by relatively less inflammation compared to adults; therefore, research aimed at reducing the inflammatory process related to wound healing might speed healing and improve the final s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 89 publications
4
104
0
2
Order By: Relevance
“…2 However, some cutaneous wounds involves complex inflammatory processes, which can lead to a more aggressive state and take longer time resulting in chronic state of inflammation. 3 Diabetic wounds are complex wounds appear as cuta neous complications arise from uncontrolled diabetes mellitus caused by hyperglycemia, oxidative stress and /or microbial infections. 45 Practices and compounds that arise from traditional medicine have been used to create the optimal condi tions for the skin regeneration process and to prevent the failure of the healing process, according to the origin, these therapies are classified into herbal and animalderived compounds.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, some cutaneous wounds involves complex inflammatory processes, which can lead to a more aggressive state and take longer time resulting in chronic state of inflammation. 3 Diabetic wounds are complex wounds appear as cuta neous complications arise from uncontrolled diabetes mellitus caused by hyperglycemia, oxidative stress and /or microbial infections. 45 Practices and compounds that arise from traditional medicine have been used to create the optimal condi tions for the skin regeneration process and to prevent the failure of the healing process, according to the origin, these therapies are classified into herbal and animalderived compounds.…”
Section: Introductionmentioning
confidence: 99%
“…These opinion was also consistent with the statement that fibroblasts can differentiate into myofibroblasts, the which are responsible for collagen deposition and wound contraction. 45 Previous study showed that the faster collagen synthesis, then the sooner of wound healing. Beside that locally collagen synthesis in need of oxygen and other nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…PDT at the intermediary dose promoted the increase of approximately 20% in collagen and elastin, as well as in MMPs expression, which was not reached using only light. The photobiomodulation effect was observed even in the first 7 days after irradiation, but the most prominent was reached after 14 days [72].…”
Section: Pdt On Wound Healingmentioning
confidence: 94%